Congenital Toxoplasmosis: The Unknown Disease Burden of Pregnant Women in Southeast Asia - Salibay, Cristina Cabanacan; Torres, Mario S.; Salibay, Steven Paulo C.; Nissapatorn, Veeranoot (Journal of Pediatric Infectious Diseases, 2017)
Congenital toxoplasmosis (CT) is caused by Toxoplasma gondii which is an Apicomplexa parasite that requires a cat for its sexual cycle and a wide array of warm-blooded animals, including man for its asexual cycle. CT develops due to vertical transmission of the parasite from an infected mother to the child. It is in this manner when the unborn child becomes susceptible to infection. The literature review revealed that 26.0% of infants born from T. gondii infected mother are subclinically infected at birth and 10.0% are either mildly or severely clinically affected, while 3.0% of neonates die. Predominant manifestation of CT is encephalomyelitis, initiated by formation of microglial nodules in the brain. However, the most remarkable classical triad signs of toxoplasmosis are hydrocephalus or microcephalus, intracranial calcification, and retinochoroiditis. Hence, this review focused on the risks of the child from developing CT, the role of the pregnant women on the transmission of the parasite, and the risks of acquiring the parasite by the expectant mothers from Southeast Asia vis-à-vis transmitting the same to the unborn child. Likewise, this review also included the methods used for the diagnosis of CT and its importance in early detection and management of the disease by assessing practical means of controlling the incidence and preventing further transmission of the parasite.
Keywords: congenital toxoplasmosis; pregnancy; Toxoplasma gondii; Southeast Asia